Relationship between Halal Tourism and Gender: Empirical Studies in Pekalongan, Central Java - Kuat Ismanto (Al Qalam, 2023)
The paper aims to analyze the practice of gender position in halal tourism in the Pekalongan area. This study is categorized as field research with a qualitative approach. The study's primary data were collected through observations of tourist destinations/objects, including culinary tourism, historical-cultural tourism, religious tourism, and artificial/special interest tourism. In addition, interviews were also conducted with tourist attraction managers and tourists visiting destinations/tourist taxis in the region. Secondary data is collected through the study of books, journal articles, research reports, and others. The data collected were analyzed descriptively and qualitatively. The results of this study indicate that the implementation of tourism in Pekalongan City has involved the participation of women in management. On the other hand, the manager also provides special tourist facilities for women, such as lactation rooms, toilet separation, and others. However, the quality and quantity need to be added and improved. In general, the implementation of tourism in Pekalongan has tried to fulfill gender equality in employment and the provision of facilities. Tourism that upholds gender equality follows the concept of halal tourism.